Measurement plus observation – A new structure in metrology. (October 2018) - Ruhm, Karl H.
Abstract: The diverse fields of customary Metrology reveal dissimilar perceptions concerning the meaning of the classical procedure «measurement» and of the trendy procedure «observation». No integrating consensus for a common source of insight in Metrology is visible yet. The following endeavour shall be a systematic attempt concerning current data and information gathering tasks and structures. It will propose and develop a self-evident definition of the combination of both procedures in Metrology, "measurement plus observation", and will reveal their stringent logical and analytical relationships. Reasonably, dynamic systems and subsystems can model and visualise this structurally demanding result within Signal and System Theory best. The complementary tasks of measurement plus observation constitute a modern, consistent, and extended version of the basic metrological structures and needs. This quantitative approach, supported by elucidating Signal Relation Diagrams, is quite new. In order to avoid useless discussions concerning contradictory terms, one should use the term «metrological observation» in case of doubt.